Vibration AM-FM sidebands mechanism of planetary gearbox with tooth root cracked planet gear. (July 2022) - Yang, Xiaoqing; Wang, Liming; Ding, Kang; Ding, Xiaoxi
Highlights: FM models of transfer path and projection function of cracked planet are built. AM-FM phenomenon models with fault-induced speed fluctuation are developed. Vibration AM-FM sidebands of planet gear with tooth root crack are deduced. Experiment results agree well with those obtained from the phenomenon models. Abstract: The planet gear crack induced speed fluctuation is fully considered in the three effect factors of vibration signal like path weighting function, meshing forces and the measured-direction projection function. A series of phenomenon models of the vibration AM-FM signals of planet gear with tooth root crack are then developed by introducing three effect factors. The vibration AM-FM sidebands of cracked planet gear are finally obtained from the models, which are classified into two clusters that respectively locate at whole frequency range and harmonics of the meshing frequency. Harmonics of the fault feature frequency in the whole frequency range are modulated by the rotation frequency of carrier, which is obvious in the resonance ranges. Besides, harmonics of the meshing frequency are modulated by the fault feature frequency to form fault modulation sidebands, which are further modulated by the rotation frequency of carrier. The experimental results agree well with those obtained from the phenomenon models. The vibration signal models considering the cracked fault induced speed fluctuation perfect the models only containing the fault AM effect. The improved models clearly explain the sources of complicated vibration modulation sidebands even with small amplitudes, which provide a reliable theoretical basis for the detection of planet gear with tooth root crack.